Aguja Canyon – New approach added to the structural and morphological model in the continental margin of the Colombian Caribbean - Santos Barrera, Yerinelys; Calderón Grande, María Fernanda; Gutiérrez Rincón, Eliana; Vargas Morales, Johanna P. (The International Hydrographic Review, 2025)
On the submerged continental margin of the Colombian Caribbean, the Aguja submarine canyon stands out, a structure formed by denudation processes that crosses the continental shelf and transports sediments to the deep waters in the Colombia basin. Using new hydrographic data and bathymetric analyses, this study shows a physical characterization of the canyon, which stretches for more than 197 km with depths of 10 m to 3,783 m and a width of 1 km to 8 km. Four segments controlled by regional structural geology are identified, each with a distinct channel direction. Aguja Canyon shows instability in its walls and surroundings with landslides, faults and mud volcanism, evidencing considerable tectonic and sedimentary activity along the continental margin.